PROBLEMS IN THE SCIENTIFIC STUDY OF THE HISTORY OF CRAFT OF SURKHANDARYA REGION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article talks about the history of the study of the history of oasis crafts from the southern regions of Uzbekistan, namely in the Surkhandarya region in the years 1950-1980 in scientific research. Also, according to the geographical determination of Surkhondarya region, the spread of handicrafts across the oasis is explained on the basis of scientific literature.